2001
DOI: 10.1002/1521-4095(200104)13:8<580::aid-adma580>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions and Stabilization of the Organized Hybrid Langmuir-Blodgett Films of Alkanoic Acids/CdS and PbS Q-Particles

Abstract: Identification of the phase transition (see Figure) that occurs at the early stages of the topotactic transformation of Langmuir–Blodgett films of Cd or Pb behenate and arachidate with H2S has led to clarification of the structures of the hybrid films, previously in question. The ordered phase is stabilized by the addition of thio‐carboxylic acids to the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Nanocrystallites of semiconductors and conducting metals that display quantum‐size effects, referred to as quantum particles (Q‐particles), are attracting great interest owing to their unique optoelectronic properties 14. Recently, it was demonstrated that organization of the Q‐particles in periodic patterns can lead to cooperative properties not shown by the individual components of the composite 511. In recent years, different methodologies have been followed for the preparation of organized composites.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystallites of semiconductors and conducting metals that display quantum‐size effects, referred to as quantum particles (Q‐particles), are attracting great interest owing to their unique optoelectronic properties 14. Recently, it was demonstrated that organization of the Q‐particles in periodic patterns can lead to cooperative properties not shown by the individual components of the composite 511. In recent years, different methodologies have been followed for the preparation of organized composites.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In the past few years, significant progress has been made on these materials, and various approaches have been reported to synthesize inorganic-organic hybrid nanomaterials, such as micelle and microemulsion templates, 5 sol-gel process, 6 sonochemistry, microwave radiation, 7 biomimetic method, 8 LangmuirBlodgett (LB) method, 9 hydrothermal, 2 solvothermal 10 and others. As the representative of these materials, polymer/ metal chalcogenides nanocomposites have been extensively investigated because of their great potential in optoelectronic applications in the fields of light-emitting diodes (LEDs), solar cells, sensors and optical recording materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hybrid composite of sulfonated polystyrene (PS) matrix was prepared through in situ CdS nanoparticles growing;4 CdS nanoparticles were incorporated into polyacrylamide hydrogel by swelling and shrink cycles to obtain polymeric composite;5 CdS nanocomposite were fabricated on the different polymer matrix such as polyacrylamide,6 dendrimers,7 polymer micelles,8–10 and layer‐by‐layer polyelectrolyte 11. The organic‐inorganic hybrids Langmuir‐Blodgett films were prepared via topotactic gas‐solid reaction with H 2 S 12,13. At the same time, biomacromolecules have been utilized to fabricate CdS nanocomposites, such as the chaperonin proteins wrapping CdS as high thermal and chemical stability semiconductor nanocrystals,14 porous cellulose fibers also have been employed as an effective nanoreactor as well as particle stabilizer for in situ synthesis of metal nanoparticles from metal precursor solution 15,16.…”
Section: Introductionmentioning
confidence: 99%